Ajaran Hadis Qudsi tentang Anjuran Infak: Analisis Teologis, Etis, dan Sosial dalam Konteks Kontemporer - Hayatun Nissa; Anisa Tufahati; Muhammad Akmansyah (Al-Kindi, 2026)
The Hadith Qudsi, conveying Allah’s words through the Prophet Muhammad, is a unique source of Islamic guidance emphasizing infaq (spending in the way of Allah). This study examines fundamental qudsi hadiths, including the fifth hadith: “O My servants, spend, and I shall spend on you,” alongside others that encourage generosity, prohibit hoarding, and affirm Allah’s ownership of sustenance. Through a qualitative literature review, the research explores theological (trust in sustenance, divine ownership, promised reward), ethical (sincerity, empathy, self-restraint), and social dimensions (wealth distribution, solidarity, and sustainable development). The findings highlight the continuing relevance of infaq in addressing modern challenges, positioning it as a pillar of Islamic philanthropy and a means to achieve Sustainable Development Goals (SDGs) such as poverty eradication (SDG 1), food security (SDG 2), and quality education (SDG 4). Moreover, it underscores the adaptation of infaq within the digital economy as an effective tool for crisis response and community empowerment. Ultimately, infaq is presented as a holistic, transformative act of worship that integrates spiritual and social values, fostering justice, compassion, and sustainability in contemporary society.